Percepción del paciente adulto de la calidad de atención y trato humanizado del profesional de enfermería, Cajamarca-2020 - Pacheco Flores, Haydee (2021)
Objective: To determine the relationship between adult patient perception of the quality of care and humanized treatment provided by the nursing professional, Cajamarca-2020. Material and method: Basic type study, with a descriptive correlal, non-experimental and transversal level, the sample was 186 adult patients, who responded to two questionnaires with characterization variable and two Likert type instruments of 12 items for patient perception and 14 items for the humanized treatment variable. The results were presented descriptively and inferentially. Results: It was observed that 53.23% of patients have poor technical perception, 32.26% regular and 14.52% have a good perception, as well as 54.84% of patients receive regular humanized treatment, 24.19% poor and 20.97% have a good perception. Conclusions: The results obtained in the correlation reflect that there is a positive relationship of 0.445 between adult patient perception of the quality of care and humanized treatment; that is to say that at a better perception of the adult patient there will be better humanized treatment. Key words: Perception, humanized treatment, communication, nurse qualities.